2011
DOI: 10.1007/s11746-011-1843-7
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of γ‐Linolenic Acid and Stearidonic Acid Biosynthesis During a Life Cycle of Borago officinalis L.

Abstract: This study investigated the levels of c-linolenic (GLA, 18:3n-6) and stearidonic acid (SDA, in various parts of the borage plant (Borago officinalis L.) to elucidate D6-desaturase activity. Lipid class and fatty acid (FA) composition during germination of the seeds and FA composition of various borage parts were determined as well as FA compositions of neutral lipids (NL), polar lipids (PL), glycolipids (GL) and monogalactosyl diacylglycerols (MGDG) of borage leaves. When seeds were germinated for 12 days in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 34 publications
0
11
1
Order By: Relevance
“…The high level of GLA is found usually in seed oils of several plant species. It is also found in various organs such as leaves, flowers, stems and roots of some plant species [43,44,45,46,47]. However, the synthesis and accumulation of GLA in organs largely depend on plant species, genotype, growth stage, and environmental factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high level of GLA is found usually in seed oils of several plant species. It is also found in various organs such as leaves, flowers, stems and roots of some plant species [43,44,45,46,47]. However, the synthesis and accumulation of GLA in organs largely depend on plant species, genotype, growth stage, and environmental factors.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, a considerable level of GLA was found in M. maritima . The GLA content in the leaf tissues (14.05%) of in vitro-developed shoots was also greater than that found in the leaves of Borago officinalis (2.5–6.5%), Delphinium gracile (0.033%), Epilobium hirsutum (1.4%), Epilobium lanceolatum (0.81%), Myosotis nemorosa (1.45%), Primula cortusoides (4.0%), Primula denticulata (5.9%), Primula farinosa (5.4%), Primula glaucescens (6.0%), Primula luteola (1.9%), Primula marophylla (5.7%), Primula malacoides (10.9%), Primula scotica (6.7%), Primula vulgaris (0.6%), Primula vialii (1.5%), and Scrophularia sciophila (0.3%); stems of Borago officinalis (10.1–11.5%), Cynoglossum creticum (4.07%), Scrophularia sciophila (0.7%); roots of Borago officinalis (13.7%), Cynoglossum creticum (7.16%), Echium creticum (2.9%), Primula cortusoides (1.9%), Primula denticulata (0.2%), Primula farinosa (0.1%), Primula glaucescens (0.3%), Primula luteola (0.6%), Primula marophylla (0.4%), Primula malacoides (1.4%), Primula scotica (0.2%), Primula vulgaris (0.8%), Primula vialii (0.1%), S. sciophila (0.27%); and flowers of Anchusa azurea (3.56%), and Scrophularia sciophila (0.28%) [43,44,45,46,47].…”
Section: Discussionmentioning
confidence: 99%
“…MGDG is a proposed substrate of the lipid synthesis enzyme Δ6‐desaturase in the terrestrial plant borage (Griffith, Brechany, Jackson, Christie, Stymne & Stobert ; Staehler et al . ). The Δ6‐desaturase is a key enzyme in the production of n‐3 LC‐PUFA in eukaryotic and vertebrate systems.…”
Section: Discussionmentioning
confidence: 97%
“…Lipid classes were separated using SPE silica columns (GracePure e silica 1000 mg/6 mL from Grace Davison Discovery Sciences, Baulkham Hills, NSW, Australia) by following the elution protocol according to Stern and Tietz (1993) with minor modifications (Staehler, Quek & Miller 2011). The columns were first conditioned with 17.5 mL chloroform before they were loaded with approximately 20 mg of oil.…”
Section: Determination Of Lipid Classes and Fatty Acid Compositionmentioning
confidence: 99%
See 1 more Smart Citation